Penerapan Strategi Pemasaran dalam Meningkatkan Omset Penjualan Jajanan Lokal UMKM di Kota Mataram - Rini Anggriani; Anthony Anggrawan; Gusti Ayu Dasriani; Raden Bagus Faizal Irani Sidharta; Dafa Awanta; Jean Suciasti Gunawan (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Micro, Small and Medium Enterprises (MSME) sector is one of the important sectors as the main support for the community's economy.However, the Covid-19 event had a significant impact on this sector.Indeed, Covid-19 has subsided, but the impact of this phenomenon is still affecting all sectors, one of which is the Micro, Small and Medium Enterprises (MSME) sector. This service program is carried out on local snack products in the city of Mataram with the target of helping increase sales turnover of The Micro, Small and Medium Enterprises (MSME) products through optimizing the application of mix marketing strategies. The method used is a qualitative descriptive approach with data processing techniques using triangulation.The results of this service show that the application of the marketing mix marketing strategy that is carried out can have a positive and effective impact on increasing the sales turnover of The Micro, Small and Medium Enterprises (MSME) products in the city of Mataram.